Analysis and Design of a Novel Multiband Antenna for Mobile Terminals - Yuan Yao; Wanzhong Chen; Xiaodong Chen; Junsheng Yu (International Journal of Antennas and Propagation)
A multiband planar terminal antenna with a compact size of 40 mm × 24 mm is proposed in this paper. This antenna consists of a monopole patch with two slots on it and a meandering strip loaded on the top. Two parasitic stubs and a branch on the ground are used to adjust and widen the impedance bandwidth of the antenna. Simulations and measurements are carried out to study the antenna performances in terms of impedance matching, efficiency, gain, and radiation patterns. Both of simulation and measurement results are shown to illustrate the good performance of the proposed antenna. The antenna can operate at 450–474 MHz, 860–1040 MHz, 1705–2428 MHz, and 2500–2710 MHz. These operating bandwidths cover GSM900, DCS, PCS, UMTS, LTE2500, and LTE’s low frequency band (450–470 MHz). It is very suitable for multifunctional terminal applications in wireless communication systems.